Patellar tendinopathy outcome predictors in jumping athletes: feasibility of measures for a cohort study - Tayfur, A.; Salles, J. I.; Miller, S. C.; Screen, H.; Morrissey, D. (Physical Therapy in Sport, 2020)
Highlights: • Online use of a PROM questionnaire battery was similar to traditional administration. • Collecting training load with shorter recall duration should improve accuracy and feasibility. • The graded loaded challenge is suitable for further clinical testing.